(untitled) (KYAMC Journal, 2020)
Background: Neonatal sepsis is one of the leading causes of neonatal mortality and morbidity globally, more in developing countries. Frequent monitoring of changing pattern of pathogens causing neonatal sepsis is mandatory for effective treatment. Objectives: This study was done to isolate and identify different organisms of sepsis and to compare different types of organisms between early-onset neonatal sepsis (EONS) and late-onset neonatal sepsis (LONS). Materials and Methods: This cross sectional descriptive study was conducted in Department of Microbiology in collaboration with Department of Neonatology, (DMCH) Dhaka. Blood sample was collected from 106 clinically suspected septicemic neonates and isolation and identification of organism was done by automated blood culture and standard microbiological protocol. Data was collected from attendants by filling a predesigned questionnaire. Results: Among 106 samples, 76 (71.69%) were bloodculture positive. Prevalence of (LONS) was higher 42 (55.26%) in comparison to (EONS) 34 (44.74%). Male neonates were affected more 42 (55.26%) than female 34 (44.74%). Among the isolated organisms, Enterobacter spp. was the predominant organism 20 (26.31%) followed by Klebsiella pneumoniae 18 (23.68%) and Candida spp. 12 (15.79%). Conclusion: Gram-negative organisms play the leading role for causing neonatal sepsis and Enterobacter outbreak should be concerned. Therefore, regular surveillance of organism profile causing neonatal sepsis is of utmost necessity. KYAMC Journal Vol. 11, No.-1, April 2020, Page 14-20